Avaliação e monitoramento de QoC em sistemas cientes de contexto - MUNIZ, Luiz Carlos Melo (2017)
Quality of Context (QoC) is a concept that can be used to characterize both the quality of information (QoI) and the quality of the context data distribution service (QoS). In order to be able to also meet QoC requirements, conventional context middleware systems need to be extended. This means that their interfaces, services, and architectures must be modified to consider new context-quality requirements. Some IoT applications may have more complex QoC requirements than others. This complexity is greater when applications require multiple QoC parameters considering both dimensions (QoI and QoS), which are not always supported by the middleware layer. In addition, more comprehensive QoC support requires middleware functionality such as QoC parameter evaluation, querying, service discovery, filtering, and QoC-based context information monitoring. A middleware solution able to handle all these challenges is not yet available. With the objective of contributing to the state of the art in the development of middleware with QoC support, this master’s work proposes components capable of evaluating, filtering and monitoring the QoC with support to several parameters of data quality/sensors.